Overpressure blast injury-induced oxidative stress and neuroinflammation response in rat frontal cortex and cerebellum - OKTAY, NİHAL ŞEHKAR (ELSEVIER SCIENCE BV, 2018)
Background & aim: Overpressure blast-wave induced brain injury (OBI) and its long-term neurological outcome pose significant concerns for military personnel. Our aim is to investigate the mechanism of injury due to OBI. Methods: Rats were divided into 3 groups: (1) Control, (2) OBI (exposed 30 psi peak pressure, 2-2.5 ms), (3) Repeated OBI (r-OBI) (three exposures over one-week period). Lung and brain (cortex and cerebellum) tissues were collected at 24 h post injury. Results: The neurological examination score was worse in OBI and r-OBI (4.2 +/- 0.6 and 3.7 +/- 0.5, respectively) versus controls (0.7 +/- 0.2). A significant positive correlation between lung and brain edema was found. Malondialdehyde (index for lipid peroxidation), significantly increased in OBI and r-OBI groups in cortex (p < 0.05) and cerebellum (p < 0.01-0.001). The glutathione (endogenous antioxidant) level decreased in cortex (p < 0.01) and cerebellum (p < 0.05) of r-OBI group when compared with the controls. Myeloperoxidase activity indicating neutrophil infiltration, was significantly (p < 0.01-0.05) elevated in r-OBI. Additionally, tissue thromboplastin activity, a coagulation marker, was elevated, indicating a tendency to bleed. NGF and NF-kappa B proteins along with Iba-1 and GFAP immunoreactivity significantly augmented in the frontal cortex demonstrating microglial activation. Serum biomarkers of injury, NSE, TNF-alpha and leptin, were also elevated. Conclusion: OBI triggers both inflammation and oxidative injury in the brain. This data in conjunction with our previous observations suggests that OBI triggers a cascade of events beginning with impaired cerebral vascular function leading to ischemia and chronic neurological consequences.
Keywords: Overpressure blast injury; Brain; Trauma; Lung; Edema; NGF; NF kappa B; GFAP; Iba1; NSE; TRAUMATIC BRAIN-INJURY; SUBARACHNOID HEMORRHAGE; BARRIER PERMEABILITY; BLOOD; MODEL; INFLAMMATION; DAMAGE; EXPRESSION; BIOMARKERS; SEVERITY